MASS MEDIA MESSAGES AND DOMESTIC VIOLENCE IN NIGERIA (2016)
Mass media has saturated the industrialized world. The television in the living room, the newspaper on the doorstep, the radio in the car, the computer at work and the fliers in the mailbox are just a few of the media channels daily delivering news, opinion, music and other forms of mass communication. These days, abuse messages are preoccupied with grabbling attention and sustaining interest, rather than transferring persuasion messages. This has largely been due to a perception to build women’s self-confidence, discourage men from gender-based violence, and to make society take notice and speak up instead of look away. This article therefore shows the portrayals of women in different messages in the media. Against these backdrops of emerging trends globally and in Nigeria, this article provides an insightful ethnography of mass media messages directed at eradicating domestic violence and as a tool for advocating for violence against women and more specifically, to promote awareness of and to prevent domestic violence in Nigeria.